Early and long-term outcomes after manual and remote magnetic navigation-guided catheter ablation for ventricular tachycardia. (1st May 2018) - Qian, Pierre; De Silva, Kasun; Kumar, Saurabh; Nadri, Fazlur; Samanta, Rahul; Bhaskaran, Abhishek; Ross, David; Sivagangabalan, Gopal; Cooper, Mark; Kizana, Eddy; Davis, Lloyd; Denniss, Alan Robert; et al.
Abstract: Aims: Remote magnetic navigation (RMN) is a safe and effective means of performing ventricular tachycardia (VT) ablation. It may have advantages over manual catheter ablation due to ease of manoeuvrability and catheter stability. We sought to compare the safety and efficacy of RMN vs. manual VT ablation. Methods and results: Retrospective study of procedural outcomes of 139 consecutive VT ablation procedures (69 RMN, 70 manual ablation) in 113 patients between 2009 and 2015 was performed. Remote magnetic navigation was associated with overall higher acute procedural success (80% vs. 60%, P = 0.01), with a trend to fewer major complications (3% vs. 9% P = 0.09). Seventy-nine patients were followed up for a median of 17.0 [interquartile range (IQR) 3.0–41.0] months for the RMN group and 15.5 (IQR 6.5–30.0) months for manual ablation group. In the ischaemic cardiomyopathy subgroup, RMN was associated with longer survival from the composite endpoint of VT recurrence leading to defibrillator shock, re-hospitalization or repeat catheter ablation and all-cause mortality; single-procedure adjusted hazard ratio (HR) 0.240 (95% CI 0.070–0.821) P = 0.023, multi-procedure HR 0.170 (95% CI 0.046–0.632) P = 0.002. In patients with implanted defibrillators, multi-procedure VT-free survival was superior with RMN, HR 0.199 (95% CI 0.060–0.657) P = 0.003. Conclusion: Remote magnetic navigation may improve clinical outcomes after catheter ablation of VT in patients with ischaemic cardiomyopathy. Further prospective clinical studies are required to confirm these findings.